PENGARUH INDEPENDENSI DAN KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT INTERNAL - Permatasari, Intan (Accounting Study Program, Faculty of Economics and Business, Langlangbuana University Bandung, 2018)
This study was conducted to examine the effect of professionalism and Auditor competence on the performance of internal auditors. The purpose of the study is to know that with the  professionalism and competence of auditors Can improve the performance of internal auditors. This research was conducted at CV Fortuna Shoes. The population in this study are auditor, finance department and Accounting who work in CV. Fortuna Shoes. Sampling technique Performed with Simple Random Sampling with the spread of questionnaires Direct and obtained the number of samples of 32 respondents. Method of data retrieval The primary used is the questionnaire method. Analysis method used To test the hypothesis is multiple linear regression. Thestatistical method Used to test the classical assumptions first, to test the hypothesis then used is t test and processed by using SPSS program 23.0 For Windows. The results showed the influence of professionalism on performance Internal auditor of 20.16%. The internal auditor has an attitude Professionalism will have a good impact on performance as it gets higherProfessionalism, the higher the auditor's performance. Influence of competence To the performance of internal auditors of 35.28% due to auditors who have High competence capable of producing good performance. Research result The influence of professionalism, the competence of auditors on the performance of internal  auditors Amounted to 39.06%, it shows that the better the attitude of professionalism And have adequate competence then the better the performance generated.